Item analysis of reading comprehension questions for English proficiency test using Rasch model - Dewi, Henda Harmantia; Damio, Siti Maftuhah; Sukarno, Sukarno (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
The need to take English as a foreign language proficiency test (known as TOEFL [Test of English Language Proficiency]) has been gaining popularity in Indonesia. The increasing demands for such a test and its expensive cost have reinforced many institutions to develop TOEFL instruments and administer the test internally. However, constructing a test instrument is a complex process that makes conducting item analysis become more challenging. Meanwhile, item analysis is crucial to assess the items' quality. Therefore, this study reported the results of statistically analyzing 20 questions of TOEFL reading comprehension that were analyzed in terms of the test reliability, the item and person fit, and the items' difficulty level. Thirty-eight members of the English Department Students' Association of a state university in West Java participated in this study by taking the reading test. The data were analyzed using the Rasch model by utilizing the Quest program. The results showed that four items (36.8%) did not fulfill the ideal criteria of a valid test because they were too easy and too difficult to be given to the target test takers; thus, they needed to be discarded. Meanwhile, 16 items (63.2%) are of good quality and can be used immediately in the proficiency test, especially to measure reading comprehension skills, because they have fulfilled the standard requirements for a valid test. The findings have provided insight into the importance of item analysis in validating test instruments to improve the test quality for future administrations.